Charge-transfer dynamics at a Ag/Ni-MOF/Cu2O heterostructure in photoelectrochemical NH3 production. Issue 65 (22nd July 2021) - Liu, Ying; Lu, Jianmin; Zhang, Qianxiao; Bai, Yajie; Pang, Xuliang; Wang, Song; Bai, Hongye; Fan, Weiqiang
Abstract : The charge-transfer dynamics of Ag/Ni-MOF/Cu2 O were first demonstrated by ultrafast transient absorption spectroscopy. DFT calculations further reveal the superior pathway for N2 reduction over the unsaturated Ni 2+ sites. Abstract : Ag-decorated ultrathin Ni-MOF on Cu2 O was fabricated for the first time. The charge-transfer dynamics at the heterostructure was studied by ultrafast transient absorption spectroscopy in depth. An NH3 yield rate of 4.63 μg h −1 cm −2 with a faradaic efficiency of 24.3% has been achieved. DFT calculations further supported to further comprehend the nitrogen reduction reaction mechanism.